Developing multimedia for reading instruction - Pratiwi, Erita Budi; Wiedarti, Pangesti (LingTera, 2021)
This research study aimed to (1) develop multimedia for reading instruction for the ninth-grade students at SMP N 1 Kalasan, and (2) find out the quality of multimedia for reading instruction for the ninth-grade students at SMP N 1 Kalasan. This research study applied research and development adapted from Lee & Owens (2004). The development of multimedia in this study was conducted in four stages: analysis, design, development, and evaluation and revision. Data were obtained through questionnaires. The collected data were analyzed by means of descriptive statistics. The findings showed that the quality of the developed multimedia for reading instruction for the ninth-grade students at SMP N 1 Kalasan was "good" in terms of instructional and material aspects (with average scores 4.17 and 4.10) respectively, and "excellent" in terms of media aspect (average score 4.23). In terms of those three aspects, the developed multimedia was categorized as "good" with an average score of 4.16.